Dual-polarized band-absorptive frequency selective rasorber using meander-line and lumped resistors - Yu, Weiliang (2021)
A novel dual-polarized band-absorptive frequency selective rasorber (FSR) is proposed in this communication. The FSR is constructed by two-layer cascaded printed circuit boards, in which meander-line square loops with and without lumped resistors loaded on the top and bottom surfaces of the two substrates. Its operating principle is analyzed, and an accurate equivalent circuit model is presented. A prototype has been fabricated, assembled, and measured. The measured absorption band is from 4.8 to 6.81 GHz (34.6%), with a thickness of λ a /8 at 4.8 GHz. Moreover, it is almost transparent to electromagnetic waves below 1.54 GHz. The measurement results achieve a good agreement with the simulated results, which verifies the effectiveness of the design.